Mitotic and labelling activity in normal human epidermis in vivo - Camplejohn, R S; Gelfant, S; Chalker, D; Sittampalam, Y (Cell and tissue kinetics, 1984)
Labelling and mitotic indices were studied in the epidermis of twenty-eight young men. A mean labelling index of 5.5% was found from the whole study and a mean mitotic index of 0.06%. Mitotic index particularly was extremely variable; indices between 0.002 and 0.438% were found in individual biopsies. In the first two of three experiments in which mitotic index at 09.00 hours was compared with that at 15.00 hours, significant differences were found (15.00 hours greater than 09.00 hours by a factor of 2.6, P less than 0.001). However, in the third such experiment no such difference was found, suggesting that the timing and occurrence of diurnal rhythms of mitotic activity may not be consistent in normal human epidermis. In the one experiment in which it was investigated, a significantly higher mitotic index was found at 21.00 hours compared to 09.00 and 15.00 hours. Labelling index did not vary significantly at 09.00, 15.00 or 21.00 hours. However, labelling index did show a significant pattern of change over a 12-month period in two groups of subjects; peaks of labelling were seen in July and troughs in January. Very high ratios of labelled: mitotic cells were found, the median ratio for the whole study being ninety-eight labelled: one mitotic cell. This finding supports the possibility that not all labelled cells subsequently go on to divide in normal human epidermis.